Indonesia’s Personal Agentic Potential in Encounter-Recovery of the Spread of Covid-19: a Study of an Islamic Agentic Awareness - Alfaiz, Alfaiz; Fatia, Azharia; Syarqawi, Ahmad; Wiryawan, Ryzki; Rafiola, Ryan Hidayat; Inayah, Asitah Nurul; Elsyad, Muhammad Khafiyyan; Costa, Augusto Da (Psikis : Jurnal Psikologi Islami, 2024)
This study explores Indonesia's personal agentic potential in addressing the spread of Covid-19 by implementing various government policies and Islamic agency awareness. Expost facto was used in this research, complemented with literature analysis. Data were collected from 200 respondents, classified based on education and gender. The data were validated using the Social and Agentic Awareness Questionnaire (SAAQ) and descriptors. The results showed that 76% of the respondents with secondary education had agentic and agent awareness of the virus and 24% did not. However, in terms of gender, 68% and 32% of male and female respondents had appropriate agentic awareness. Similarly, 60% of respondents with higher education and 40% with middle/secondary education had social awareness, in accordance with 35% of female and 65% of male respondents. These results indicated that respondents from higher education have a greater influence and potential in social awareness and agents to deal with the spread of COVID-19 compared to respondents from middle/secondary education. Subsequently, regarding agentic awareness, female respondents have lower social awareness compared to male respondents.